Implementasi Penggunaan Media Pembelajaran Wordwall pada Hasil Belajar Bahasa Arab Kelas XI di MAN 1 Kabupaten Bogor - Siti Afifah; Indry Yunizul Pesha; Asep Gunawan (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This study discusses effective and innovative learning media to improve students' interest and learning outcomes. Interest in learning is the desire to do something because of interest and pleasure in doing it, including in terms of learning. Learning also requires learning media to help the teaching and learning activities take place. Learning media is a tool that can be used to help the learning process to be effective and innovative. Wordwall is a network-based digital gamification application that is useful as a learning resource, learning media, and a fun assessment tool for students. With the aim of knowing the implementation of the use of wordwall learning media in Arabic language learning, knowing how students learn Arabic with carrot learning media, knowing whether there is an increase in the use of learning media in the Arabic language learning process and knowing the learning outcomes of students using wordwall learning media. This study uses a qualitative descriptive analysis approach through interviews and documentation. The results of the study show that wordwall learning media can provide benefits and good things such as increasing students' enthusiasm and motivation in learning in learning activities. In using this learning media, preparation is needed in making RPP learning media, designing interesting and appropriate types of game content and adjusting the level of difficulty. However, the obstacles in using this motorcycle learning media are the limited ability of educators to use the Word application, the lack of adequate facilities and infrastructure, and the length of time needed to prepare the material.